Step by step explanation
________________
Attachments:
![](https://hi-static.z-dn.net/files/d03/d75091499ee0836096be61c87db5dcb9.jpg)
Answers
Answered by
1
Question:-
Prove that
Required Formula:-
Solution:-
Take LHS
By using formulae
LHS becomes
=![\frac{ (\frac{ {2}^{x} }{2}) + {2}^{x} }{( {2}^{x} \times 2) - {2}^{x} } \frac{ (\frac{ {2}^{x} }{2}) + {2}^{x} }{( {2}^{x} \times 2) - {2}^{x} }](https://tex.z-dn.net/?f=+%5Cfrac%7B+%28%5Cfrac%7B+%7B2%7D%5E%7Bx%7D+%7D%7B2%7D%29+%2B++%7B2%7D%5E%7Bx%7D++%7D%7B%28+%7B2%7D%5E%7Bx%7D++%5Ctimes++2%29+-++%7B2%7D%5E%7Bx%7D++%7D++)
Take 2^x in common
=![\frac{ {2}^{x} ( \frac{1}{2} + 1) }{ {2}^{x} (2 - 1)} \frac{ {2}^{x} ( \frac{1}{2} + 1) }{ {2}^{x} (2 - 1)}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%7B2%7D%5E%7Bx%7D+%28+%5Cfrac%7B1%7D%7B2%7D+%2B+1%29+%7D%7B+%7B2%7D%5E%7Bx%7D+%282+-+1%29%7D+)
=![\frac{ \frac{1 + 2}{2} }{1} \frac{ \frac{1 + 2}{2} }{1}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Cfrac%7B1+%2B+2%7D%7B2%7D+%7D%7B1%7D+)
=![\frac{3}{2} \frac{3}{2}](https://tex.z-dn.net/?f=+++%5Cfrac%7B3%7D%7B2%7D+)
So, LHS = RHS
Hence, proved
Answered by
0
Step-by-step explanation:
Here's ur answer in the above attachment
Attachments:
![](https://hi-static.z-dn.net/files/d0f/7b1080f901438f95493274f5f394cca7.jpg)
Similar questions